1998
DOI: 10.1046/j.1365-2915.1998.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical transmission ofTrypanosoma evansiandT. congolensebyStomoxys nigerandS. taeniatusin a laboratory mouse model

Abstract: Mechanical transmission of Trypanosoma evansi (South American origin) and T. congolense of Kilifi DNA type (Kenyan origin) was studied in laboratory mice using the African stable flies Stomoxys niger niger and S. taeniatus. Altogether, 355 flies were interrupted after feeding on infected blood and then transferred immediately to an uninfected mouse to complete feeding. Microscopy and subinoculation of triturated flies into uninfected mice demonstrated the survival of T. congolense in Stomoxys for up to 210 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 18 publications
0
34
0
1
Order By: Relevance
“…In northern India, T. evansi is transmitted mechanically by biting hematophagous flies (Tabanids) (Sumba et al, 1998) and T. equi is mainly transmitted by longistrate tick, Hyalomma anatolicum anatolicum, causing significant morbidity and mortality in equids . As the vectors of both the diseases are habitual to hot plain areas of south-western Punjab, the epidemiological status of these infections in north-eastern parts of the province still remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In northern India, T. evansi is transmitted mechanically by biting hematophagous flies (Tabanids) (Sumba et al, 1998) and T. equi is mainly transmitted by longistrate tick, Hyalomma anatolicum anatolicum, causing significant morbidity and mortality in equids . As the vectors of both the diseases are habitual to hot plain areas of south-western Punjab, the epidemiological status of these infections in north-eastern parts of the province still remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The exception to this is when mechanical transmission occurs, during which pathogens are rapidly moved from insect to insect on contaminated mouth parts. One example is Stomoxys nigra Macquart, which transmit Trypanosoma evansi Steel in this way , Sumba et al 1998. The more general pattern is biological transmission, where the parasite may multiply in the insect vector, change into another developmental stage or both change and multiply Hurd 2002, Lehane 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that motile and presumably viable T. evansi remained in the proboscis of Stomoxys spp. for approximately 5-7min after feeding 15 , which could explain why T. evansi has been maintained within the camel herds without apparent infection of other surrounding livestock.…”
Section: Stomoxys Calcitransmentioning
confidence: 99%